Does environmental, social, and governance news coverage affect the cost of equity? A textual analysis of media coverage - Yu, Haixu; Liang, Chuanyu; Wang, Weiran; Liu, Xinglin (Frontiers in Public Health, 2025)
IntroductionAmid growing global environmental challenges and the pursuit of sustainable development, Environmental, Social, and Governance (ESG) has become an important framework for promoting green and responsible business practices. This paper investigates how ESG-related media coverage affects the cost of equity, with a focus on how improved information transparency can influence firms’ financing outcomes.MethodsWe construct an ESG performance index using a machine learning approach, based on ESG-related news text data and the level of media attention received by listed companies. The index is calculated by evaluating the tone (positive or negative) of each firm’s annual ESG news coverage.ResultsThe results reveal a significant negative correlation between corporate ESG media coverage and the cost of equity, where more positive coverage is associated with a lower financing cost. Mechanism analysis confirms that stronger ESG performance can reduce equity costs by enhancing the transparency of corporate information. Heterogeneity analysis further shows that this negative relationship is more pronounced in state-owned and large firms.DiscussionThe findings provide empirical evidence for the relationship between ESG news coverage and the cost of equity, validating this link in the context of an emerging market. These results offer new insights into how ESG engagement improves capital market efficiency and supports the broader goals of sustainable and responsible investment.